2014
DOI: 10.7150/ijms.7186
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Subclinical Hypothyroidism is Independently Associated with Progression of Chronic Kidney Disease

Abstract: Background and Aim: Patients with chronic kidney disease (CKD) often have subclinical hypothyroidism. However, few reports have investigated changes in the status of subclinical hypothyroidism in CKD patients and its clinical significance in CKD progression.Methods: We included 168 patients with nondialysis-dependent CKD stages 2-4. The normalization of subclinical hypothyroidism during follow-up was assessed, and the association between transitions in subclinical hypothyroid status and the rate of decline of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
2
9
1
1
Order By: Relevance
“…8 It is frequently seen in patients with chronic kidney disease/failure. 9 Also, with the decrease in glomerular filtration rate the prevalence of subclinical hypothyroidism increases. In the United States the prevalence of subclinical hypothyroidism is 4-8.5%.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is frequently seen in patients with chronic kidney disease/failure. 9 Also, with the decrease in glomerular filtration rate the prevalence of subclinical hypothyroidism increases. In the United States the prevalence of subclinical hypothyroidism is 4-8.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones influence kidney function by direct renal effects as well as systemic hemodynamic [ 16 ], metabolic, and cardiovascular effects [ 17 ]. Previous studies showed that overt and subclinical hypothyroidisms were associated with reduced eGFR and increased risk of CKD and unresolved subclinical hypothyroidism were independently associated with the rate of renal function decline [ 12 ], and thyroid hormone supplement attenuated the alterations [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overt thyroid disease is relatively uncommon in T2D, and only a few studies investigated their relationship with kidney function in T2D. Some studies have shown that overt and subclinical hypothyroidisms were associated with reduced eGFR and increased risk of CKD [ 8 11 ] and that unresolved subclinical hypothyroidism was independently associated with the rate of renal function decline [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism diminishes protein synthesis and cellular development, which leads to decreases in cell number, density, and size of the kidney [3]. It has been demonstrated that subclinical hypothyroidism might be a risk factor for faster decline of renal function [4][5][6], with possible effect on recovery or preservation of renal function with treatment [7,8]. However, this finding are controversial and the effect of low free thyroxine (LFT) levels on eGFR decline in CKD patients has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%